2022
DOI: 10.1097/wco.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in our understanding of genetic rhabdomyolysis

Abstract: Purpose of reviewThis review summarizes recent advances in our understanding of the genetics of rhabdomyolysis. Recent findingsRhabdomyolysis is the acute breakdown of myofibres resulting in systemic changes that can be life-threatening. Environmental triggers, including trauma, exercise, toxins and infections, and/or gene defects can precipitate rhabdomyolysis. A schema (aptly titled RHABDO) has been suggested for evaluating whether a patient with rhabdomyolysis is likely to harbour an underlying genetic defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Rhabdomyolysis (RM) is a complex medical disorder involving catastrophic failure of skeletal muscle homeostasis and integrity, resulting in muscle breakdown and release of muscle cytosolic content into circulation (Cabrera-Serrano & Ravenscroft, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhabdomyolysis (RM) is a complex medical disorder involving catastrophic failure of skeletal muscle homeostasis and integrity, resulting in muscle breakdown and release of muscle cytosolic content into circulation (Cabrera-Serrano & Ravenscroft, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Rhabdomyolysis (RM) is a complex medical disorder involving catastrophic failure of skeletal muscle homeostasis and integrity, resulting in muscle breakdown and release of muscle cytosolic content into circulation (Cabrera-Serrano & Ravenscroft, 2022). Rhabdomyolysis can give rise to serious health complications such as myoglobinuria, cardiac arrhythmia and acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding dystrophies, it started with dystrophinopathy and now includes ANO5, CAV3, FKRP, SGCA, and GMPPB. 17 Recessive mutations in LPIN1, as seen in a patient in the study by Wong et al, 14 have more recently been found to be a common cause of childhood-onset and severe rhabdomyolysis in the setting of catabolic stress. For example, Kahraman et al 18 reported a 5-yearold with fatal rhabdomyolysis with ventricular tachycardia and a 7-year-old with severe rhabdomyolysis, supraventricular tachycardia, and compartment syndrome.…”
Section: Hyperckemia and Rhabdomyolysismentioning
confidence: 96%
“…Regarding dystrophies, it started with dystrophinopathy and now includes ANO5, CAV3, FKRP, SGCA, and GMPPB. 17…”
Section: Hyperckemia and Rhabdomyolysismentioning
confidence: 99%
See 1 more Smart Citation